The Novel Two-Dimensional van der Waals Crystal InSe and its Magnetic Doping - Bhuiyan, Mahabub Alam (2019)
This thesis focusses on the electronic properties of the novel two dimensional (2D) van der Waals (vdW) crystal InSe. It examines the integration of InSe in graphene-based field effect transistors (FETs) and the incorporation of transition metals in InSe to create new magnetic materials. InSe is employed in graphene-based FETs as an electrically and optically active capping layer to “modulation-dope” and photosensitise an adjacent graphene layer. This leads to a “giant” quantum Hall (QH) plateau at a filling factor v = 2 in the magnetoresistance of graphene that persists over a wide range of magnetic fields. Furthermore, the optical excitation of the FETs changes the resistance of the graphene layer. The sign of the Hall voltage and of the v = 2 QH plateau persists over a wide range of temperatures of up to T ~ 200K and can be controlled by an appropriate combination of gate voltages and optical illumination. These phenomena involve the charge transfer at the InSe/graphene interface, offering opportunities for optoelectronics and quantum metrology. Also, we studied a new hybrid material system, which comprises InSe and ferromagnetic Fe-islands. We observed that unlike many traditional semiconductors, the electronic properties of pristine InSe are largely preserved after the incorporation of Fe. Also, this system exhibits ferromagnetic resonances and a large uniaxial magnetic anisotropy at room temperature, offering opportunities for the development of functional devices that integrate magnetic and semiconducting properties within the same material system.